Interleukin-1β depresses neuronal activity in the rat olfactory bulb even during odor stimulation - Adriana Jiménez; Josué Denichi Sánchez-Hernández; Viani Maya-López; Enrique Estudillo; Juan Carlos González-Orozco; Joaquín Manjarrez-Marmolejo; Nieves Herrera-Mundo; Mara A. Guzmán-Ruiz; Rosalinda Guevara-Guzmán (PLoS ONE, 2025)
The olfactory system is exposed to external and internal harmful agents that may impair the communication between the olfactory sensory neurons and olfactory brain areas. Inflammatory molecules increase in the olfactory system in response to infections and chronic systemic diseases. Interleukin-1β (IL-1β) is a cytokine produced in many inflammatory processes. In previous studies, we observed that IL-1β increased in the olfactory bulb (OB) of diabetic rats, which also presented olfactory dysfunction. This study aimed to determine whether IL-1β could be responsible for the olfactory impairment. To address this question, IL-1β and its antagonist IL-1Ra were microinjected in the OB of rats to evaluate the electrophysiological activity in the OB and entorhinal cortex (EC) by recording the local field potentials (LFPs) in resting conditions and during olfactory stimulation. RNA-seq analysis from NCBI databases demonstrated the expression of IL-1β receptor 1 (IL1-R1) in the OB from rats and mice. Interestingly, IL-1β reduced total spectral power in the OB and increased total signal frequency and gamma power in both OB and EC. Moreover, IL-1β reduced the amplitude and increased the latency of the olfactory evoked potentials (OEPs) after OB stimulation with amyl acetate. IL-1Ra microinjection before IL-1β rescued amplitude and latency of OEPs, but only partially reverted the effects of IL-1β in total spectral power and relative gamma power. In addition, IL-1Ra changed the electrophysiological activity of OB and EC; however, its effect was lower than that of IL-1β. These results suggest that IL-1β may induce olfactory dysfunction by suppressing neuronal activity in the OB and EC. Furthermore, IL-1β may also have a physiological role in the olfactory system since IL-1Ra can modify the electrical activity in these brain areas.